Antarctic Ice Sheet grounding line discharge from 1996–2024 - B. J. Davison; A. E. Hogg; T. Slater; R. Rigby; N. Hansen (Earth System Science Data, 2025)
Grounding line discharge is a key component of the mass balance of the Antarctic Ice Sheet. Here, we present a time-varying estimate of Antarctic Ice Sheet grounding line discharge, at up to monthly intervals, from 1996 through to November 2024. We calculate ice flux through 16 algorithmically generated flux gates across 998 ice sheet, glacier, ice stream and ice shelf drainage basins. We draw on a range of ice velocity and thickness data to estimate grounding line discharge. For ice thickness, we use three bed topography datasets, two firn models and a time-varying ice surface. For the ice velocity, we utilise a range of publicly available ice velocity maps at resolutions ranging from 200 m×200 m to 1000 m×1000 m, as well as new 100 m×100 m monthly velocity mosaics derived from intensity tracking of Sentinel-1 image pairs, available since October 2014. Our dataset also includes the contributions to discharge from changes in ice thickness due to surface lowering, time-varying firn air content, and surface mass change between the flux gates and grounding line. We find that Antarctic Ice Sheet grounding line discharge increased from 1999±175 to 2224±200<mspace width="0.125em" linebreak="nobreak"/>Gt<mspace linebreak="nobreak" width="0.125em"/>yr-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="89pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="5e10618e7162e47da88020537a9e7b2d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="essd-17-3259-2025-ie00001.svg" width="89pt" height="15pt" src="essd-17-3259-2025-ie00001.png"/></svg:svg> between 1996 and 2024, much of which was due to the acceleration of ice streams in West Antarctica but with substantial contributions from ice streams in East Antarctica and glaciers on the Antarctic Peninsula. The errors in our discharge dataset stem approximately equally from errors in the underlying ice velocity and thickness measurements. However, we find that the spread in possible discharge estimates depending on the choice of bed topography dataset and flux gate location is much larger than the error in any single estimate. It is our intention to update this discharge dataset each month, subject to continued Sentinel-1 acquisitions and funding availability. The dataset is freely available at https://doi.org/10.5281/zenodo.10051893 (this paper was prepared using version 7 of the dataset) (Davison et al., 2024).